Role of cytokines in pathogenesis of H. pylori induced gastric mucosal inflammation. - Badi, Manal (University of Thi-Qar Journal of Science, 2011)
Helicobacter pylori gastritis is characterized by colonize the stomach and induce strong,specific local and systemic humoral and cell-mediated immunity. The aim of this study was toevaluate the level of several cytokines and their role in the pathogenesis of H. pylori gastritisand whether H. pylori stimulate the release of these cytokines. The levels of TH1 (IFN-γ andTNF-α) and TH2 (IL-4, IL-6 and IL-10) cytokines, as well as, inflammatory cytokines (IL-1αand IL-8) were determined. Most of the investigated cytokines (IL-1α, IL-6, IL-8, IL-10, IFNγ,TNF-αand GM-CSF) showed a significantly increased level in the sera of H. pylori gastricpatients as compared to subjects (control) with no infection which showed normal seruminterleukin levels. While IL-10 showed significant decrease when compared to subjects.These results conclude the pro-inflammatory cytokines ave a central role in thepathogenesis of H. pylori-induced mucosal inflammation.